2017
DOI: 10.1136/bmjopen-2016-013719
|View full text |Cite
|
Sign up to set email alerts
|

CanWalk: a feasibility study with embedded randomised controlled trial pilot of a walking intervention for people with recurrent or metastatic cancer

Abstract: ObjectivesWalking is an adaptable, inexpensive and accessible form of physical activity. However, its impact on quality of life (QoL) and symptom severity in people with advanced cancer is unknown. This study aimed to assess the feasibility and acceptability of a randomised controlled trial (RCT) of a community-based walking intervention to enhance QoL in people with recurrent/metastatic cancer.DesignWe used a mixed-methods design comprising a 2-centre RCT and nested qualitative interviews.ParticipantsPatients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(99 citation statements)
references
References 27 publications
1
97
0
1
Order By: Relevance
“…We classified seven studies as testing psychosocial interventions that are counselling based but do not fit into the three previous categories. Two studies were focused on improving marital outcomes, while the other interventions focused on financial and legal counselling, managing weight‐ and eating‐related distress, addressing emesis, increasing physical activity through walking, and individually tailoring therapeutic approaches to meet the needs of patients …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We classified seven studies as testing psychosocial interventions that are counselling based but do not fit into the three previous categories. Two studies were focused on improving marital outcomes, while the other interventions focused on financial and legal counselling, managing weight‐ and eating‐related distress, addressing emesis, increasing physical activity through walking, and individually tailoring therapeutic approaches to meet the needs of patients …”
Section: Resultsmentioning
confidence: 99%
“…For instance, a number of studies, especially those that were underpowered for between-group comparisons, reported improved patient outcomes when comparing preintervention to postintervention scores. 15,21,23 A few studies also found improved patient outcomes in secondary outcomes 40,47,58 or at secondary time points. 21,26,67 Next, we acknowledge that our review only includes studies from the past 10 years.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Group interventions may have a temporary effect on quality of life (Clark et al., ); however, three studies (Roulston, Bickerstaff, Haynes, Rutherford, & Jones, ; Rummans et al., ; Tsianakas et al., ) reported that quality of life measures remained stable. Social support was not used as an outcome measure.…”
Section: Resultsmentioning
confidence: 99%
“…A pilot study with mixed methods (Roulston et al, 2012) appeared to have positive effects on mood and perceived health; all five participants cited social support as a useful component of the intervention. Tsianakas et al (2017) reported that questionnaires used were not sufficiently sensitive, and draws from qualitative insights to suggest that a specific social support measure be used in future work. was not identified; however, the difference in resource use appeared to be larger for participants with higher distress at baseline.…”
Section: Group Practical Interventionsmentioning
confidence: 99%
“…A variety of reports show that physical activity can reduce cancer-related morbidity and offers an important role in rehabilitation (37)(38)(39). The skeleton is sensitive to its mechanical environment, and physical stimulation contributes to maintaining bone mass.…”
Section: Discussionmentioning
confidence: 99%